1996
DOI: 10.1093/beheco/7.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Influence of helping and breeding experience on reproductive performance in the Seychelles warbler: a translocation experiment

Abstract: Reproductive success of the cooperative breeding Seychelles warbler (Acrocephalus sechellensis) increases with age. This age effect is not due to differential survival or increased reproductive effort, but to accumulated helping and breeding experience. In their first year of breeding, reproductive performance of inexperienced warblers with neither helping nor breeding experience was significandy lower than that of warblers of the same age with either previous helping or breeding experience. Reproductive perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 41 publications
2
122
0
Order By: Relevance
“…In particular, group augmentation has to be explored in much more detail if we are to understand fully the evolutionary stability of investments in the system under study. Other concepts proposed in the cooperative breeding literature may also be analysed in the same way in the future, including task sharing (Taborsky, 1994;Lacey and Sherman, 1997;Clutton-Brock et al, 2003;Arnold et al, 2005), redirected helping (Emlen, 1982;Dickinson and Hatchwell, 2004), strategic between group dispersal (Bergmüller et al, 2005a), load lightening (Crick, 1992;Heinsohn, 2004), kinship deceit (Connor and Curry, 1995), parental facilitation (of territorial inheritance) (Brown and Brown, 1984), skill acquisition (Brown, 1987;Komdeur, 1996) and between group competition (Brooke and Hartley, 1995;Cockburn, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, group augmentation has to be explored in much more detail if we are to understand fully the evolutionary stability of investments in the system under study. Other concepts proposed in the cooperative breeding literature may also be analysed in the same way in the future, including task sharing (Taborsky, 1994;Lacey and Sherman, 1997;Clutton-Brock et al, 2003;Arnold et al, 2005), redirected helping (Emlen, 1982;Dickinson and Hatchwell, 2004), strategic between group dispersal (Bergmüller et al, 2005a), load lightening (Crick, 1992;Heinsohn, 2004), kinship deceit (Connor and Curry, 1995), parental facilitation (of territorial inheritance) (Brown and Brown, 1984), skill acquisition (Brown, 1987;Komdeur, 1996) and between group competition (Brooke and Hartley, 1995;Cockburn, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of other cooperative breeding systems have similarly found little evidence that prior experience directly affects future reproductive performance (Komdeur 1996, Khan and Walters 1997, Koenig and Walters 2011, DuVal 2013.…”
Section: Discussionmentioning
confidence: 99%
“…However, some males first obtain breeding status by direct inheritance of their natal territory, and others by territorial budding, in which they begin to defend part of their natal territory and pair with a dispersing nonbreeder or a nearby widowed female. Dispersal is female-biased, but juveniles less than a year old are extremely sedentary and only rarely disperse (Woolfenden and Fitzpatrick 1984, 1996, Mumme 1992, Townsend et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Also, various scientists were encouraged to visit the island to undertake various studies of key species and processes, such as reptiles (Bourquin and Hitchins 1998), Seychelles giant millipede biology (Lawrence and Samways 2003), assessment of the invertebrates of the leaf litter and logs (Kelly and Samways 2003), spider assessments (Saaristo 1999), colonization by dragonflies (Samways 1998(Samways , 2003a, Seychelles warbler (Komdeur 1994(Komdeur , 1995 and Seychelles magpie robin biology (Komdeur 1996;LeMaitre 2002), turtle biometrics and nesting biology (Hitchins et al 2003a(Hitchins et al , b, 2004a(Hitchins et al , b, 2006, and marine assessments (Samways 2003a, b;Samways and Hatton 2001).…”
Section: The Early Phase Of Restorationmentioning
confidence: 99%